Non-Isothermal Vortex Flow in the T-Junction Pipe - Tatyana A. Baranova (MDPI AG, 2021)
The numerical simulation approach of heat carrier mixing regimes in the T-junction shows that the RANS approach is beneficial for a qualitative flow analysis to obtain relatively agreed averaged velocity and temperature. Moreover, traditionally, the RANS approach only predicts the averaged temperature distribution. This mathematical model did not consider the temperature fluctuation variations important for the thermal fatigue task. It should also be emphasized that unlike the LES approach, the steady RANS approach cannot express a local flow structure in intense mixing zones. Nevertheless, apparently the adopted RANS approach should be used for assessing the quality of computational meshes, boundary conditions with the purpose to take LES for further numerical simulation.